Neighbourhood-level socioeconomic status and prevalence of teacher-reported health disorders among Canadian kindergarten children - Janus, Magdalena; Brownell, Marni; Reid-Westoby, Caroline; Pottruff, Molly; Forer, Barry; Guhn, Martin; Duku, Eric (Frontiers in Public Health, 2024)
The evidence on the association between neighborhood-level socioeconomic status (SES) and health disorders in young children is scarce. This study examined the prevalence of health disorders in Canadian kindergarten (5-6 years old) children in relation to neighborhood SES in 12/13 Canadian jurisdictions. Methods: Data on child development at school entry for an eligible 1,372,980 children out of the total population of 1,435,428 children from 2004 to 2020, collected using the Early Development Instrument (EDI), were linked with neighborhood sociodemographic data from the 2006 Canadian Census and the 2005 Taxfiler for 2,058 neighborhoods. We examined the relationship using linear regressions. Children's HD included special needs, functional impairments limiting a child's ability to participate in classroom activities, and diagnosed conditions.The neighborhood prevalence of health disorders across Canada ranged from 1.8% to 46.6%, with a national average of 17.3%. The combined prevalence of health disorders was 16.4%, as 225,711 children were identified as having at least one health disorder. Results of an unadjusted linear regression showed a significant association between neighborhood-level SES and prevalence of health disorders (F(1, 2051) = 433.28, p < 0.001), with an R 2 of 0.17. When province was added to the model, the R 2 increased to 0.40 (F(12, 2040) = 115.26, p < 0.001). The association was strongest in Newfoundland & Labrador and weakest in Ontario.Our study demonstrated that the prevalence of health disorders among kindergarten children was higher in lower SES neighborhoods and varied by jurisdiction in Canada, which has implications for practice and resource allocation.